Ultrasound guided dry needling and autologous blood injection for patellar tendinosis. Issue 8 (26th March 2007) - James, Steven L J; Ali, Kaline; Pocock, Chris; Robertson, Claire; Walter, Joy; Bell, Jonathan; Connell, David
Abstract : Objective: To evaluate the efficacy of ultrasound guided dry needling and autologous blood injection for the treatment of patellar tendinosis. Design: Prospective cohort study. Setting: Hospital/clinic based. Patients: 47 knees in 44 patients (40 men, 7 women, mean age 34.5 years, age range 17 to 54 years) with refractory tendinosis underwent sonographic examination of the patellar tendon following referral with a clinical diagnosis of patellar tendinosis (mean symptom duration 12.9 months). Interventions: Ultrasound guided dry needling and injection of autologous blood into the site of patellar tendinosis was performed on two occasions four weeks apart. Main outcome measures: Pre- and post-procedure Victorian Institute of Sport Assessment scores (VISA) were collected to assess patient response to treatment. Follow up ultrasound examination was done in 21 patients (22 knees). Results: Therapeutic intervention led to a significant improvement in VISA score: mean pre-procedure score = 39.8 (range 8 to 72) v mean post procedure score = 74.3 (range 29 to 100), p<0.001; mean follow up 14.8 months (range 6 to 22 months). Patients were able to return to their sporting interests. Follow up sonographic assessment showed a reduction in overall tendon thickness and in the size of the area of tendinosis (hypoechoic/anechoic areas within the proximal patellar tendon). A reduction was identified in interstitial tears within the tendon substance. Neovascularity did not reduce significantly or even increased. Conclusions: Dry needling and autologous blood injection under ultrasound guidance shows promise as a treatment for patients with patellar tendinosis.